OPTIMASI PRODUKSI FRUCTOSYLTRANSFERASE OLEH Aspergillw sp. WNIC - Aris Toharisman; Triantarti Triantarti; Hendro Santoso Marantesa (BERITA BIOLOGI, 2008)
Fructo Oligo Saccharides (FOS) are considered as biologically benefit, have been developed recently to be used as functional factors in healthy foods.FOS shows low cariogenicity, nondigestibility and proliferation of bifidobacteria in human intestinal tract and dietary fiberlike action. The aim of this research is to produce FOS from sucrose by using fructocyltransferase (FT-ase) from Aspergillus sp. Research on the production of FOS was the optimization of FT-ase production. Inoculum of selected Aspergillus was added into medium with various composition and incubation conditions. Enzyme solution was mixed with sucrose and incubated at various times, pHs, temperatures and agitations.The best parameter condition was based on the highest FT-ase activity. The results showed that production of FT-ase was affected by fermentation time, pH and incubation temperature. The carbon source tested permitted good growth and enzyme production where sucrose supported rather good enzyme production.It was obvious that enzyme production was not closely correlated with cell growth.The best fructo-oligosaccharide yield (20.53%) was achieved when 20 g/100 ml sucrose was utilized. Yeast extract was good nitrogen source for enzyme production. The best FT-ase activity was achieved when 1.2 g/100 ml yeast extract was utilized. Addition of mineral salt also enhanced enzyme production where 1 g/l magnesium salt gave the best cell growth and enzyme production.